(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Artificial intelligence (AI) and machine learning (ML) have revolutionized a wide range of fields and sectors. Without explicit programming, machine learning methods allow artificial intelligence (AI) systems to examine massive volumes of data, spot trends, and make data-driven judgments. As a result, decision making has changed dramatically in industries such as marketing, banking, and healthcare, where AI can now deliver insights more quickly and accurately. Ultimately, the combination of artificial intelligence and machine learning has opened up a world of new possibilities by enabling AI systems to continuously learn, adapt, and change. Machine learning’s influence on AI is changing how companies run, how services are provided, and how issues are resolved. This signals the arrival of an era in which intelligent systems will propel innovation and advancement in every industry. This article discusses machine learning methods and impact of machine learning on artificial intelligence, such as making better decisions, personalization, data automation, and predictive analytics. Also, discusses applications of machine learning in artificial intelligence in various fields such as recommendation systems, healthcare, finance, self-driven artificial intelligence, and marketing and sales. In order for the reader to properly engage in this expanding sector, the review attempts to assist him in developing a solid knowledge basis and comprehending how these technologies impact different facets of life.